Asymptomatic bacteriuria among secondary school students - ashraf, Aisha (faculty of applied basic medical science - Libyan international medical university, 2022)
The presence of bacteria in urine is referred to as bacteriuria. It could be caused by contamination during or after urine collection, or it could indicate the presence of bacteria in bladder urine A urine sample was collected in a sterile container, the samples were cultured and incubated overnight (24 hours) to detect any observable bacterial growth the results after analyzing the numbers statistically indicated that the association between the growth of bacteria in both genders is higher in females than males which reflects the effect of gender in the appearance of asymptomatic bacteria
Keywords: Bacteriuria